A Chinese Herbal Formula Suppresses Colorectal Cancer Migration and Vasculogenic Mimicry Through ROS/HIF-1α/MMP2 Pathway in Hypoxic Microenvironment - Zong, Shaoqi; Tang, Yufei; Li, Wen; Han, Susu; Shi, Qi; Ruan, Xiaofeng; Hou, Fenggang (Frontiers in Pharmacology, 2020)
Various malignant tumors, including colorectal cancer, have the ability to form functional blood vessels for tumor growth and metastasis. Vasculogenic mimicry (VM) refers to the ability of highly invasive tumor cells to link each other to form vessels, which is associated with poor cancer prognosis. However, the antitumor VM agents are still lacking in the clinic. Astragalus Atractylodes mixture (AAM), a traditional Chinese medicine, has shown to inhibit VM formation; however the exact mechanism is not completely clarified. In this study, we found that HCT-116 and LoVo could form a VM network. Additionally, hypoxia increases the intracellular reactive oxygen species (ROS) level and accelerates migration, VM formation in colorectal cancer cells, while N-Acetylcysteine (NAC) could reverse these phenomena. Notably, further mechanical exploration confirmed that the matrix metalloprotease 2 (MMP2) induction is ROS dependent under hypoxic condition. On the basis, we found that AAM could effectively inhibit hypoxia-induced ROS generation, migration, VM formation as well as HIF-1α and MMP2 expression. In vivo, AAM significantly inhibits metastasis of colorectal cancer in murine lung-metastasis model. Taken together, these results verified that AAM effectively inhibits migration and VM formation by suppressing ROS/HIF-1α/MMP2 pathway in colorectal cancer under hypoxic condition, suggesting AAM could serve as a therapeutic agent to inhibit VM formation in human colorectal cancer.